The science of scientific agendas: insights into the agenda setting process of researchers - Santos, João Miguel da Costa Sobreiro Marques dos (2020)
Even though research agenda-setting is at the core of modern research and development activities, little is known regarding the process that leads to the definition of an agenda. The literature indirectly suggests that a series of both exogenous and endogenous factors may shape the preference of researchers concerning the research agendas they intend on pursuing – such as formal education, hierarchical position, working environment, incentives, scientific drive, creativity, risk tolerance, and personality. However, no study has been conducted in order to formally test these associations comprehensively. This project aims to identify the mechanisms underlying research agenda-setting through a multi-stage, multi-disciplinary approach. To this end, new instruments were developed – one focusing on evaluating the factors that influence research agenda setting, and another focusing on workplace related organizational aspects in the academia. Following this, Cluster Analysis was employed in order to determine the existence of overarching doctrines in terms of research agenda setting, and afterwards we explore how cognition can influence the process of research agenda setting. This was followed by an exploratory study on how the organizational setting influences these dynamics and how research agendas are also gendered. A second, more holistic, comprehensive and optimal revision of the initial research-agendas instrument concludes this project, resulting from lessons learned and knowledge acquired as the thesis was being developed. The thesis concludes with an overall discussion of the findings and its contribution to knowledge advancement, implications for practice and policymaking, and the limitations of the study, as well as an agenda for future studies.